Problem-Based Learning Using Virtual Reality Media at Islamic Senior High School in Bekasi - Sintha Wahjusaputri; Bunyamin Bunyamin; Tashia Indah Nastiti (STAI Hubbulwathan Duri, 2023)
This study aims to investigate the improvement in the quality of learning biology, especially about the anatomy of the human body after using virtual reality media “The Body VR: Journey inside a Cell”. This study employed pre-experimental research with a one-group pretest-posttest design which was chosen at random, and no stability and clarity tests were performed before the group was given treatment. According to the findings of data analysis and field research at an Islamic Senior High School in Bekasi, students struggled to understand the anatomy of the human body in biology lectures. Observation data suggest that learning outcomes remain poor, at 65%, and problem-solving abilities remain low, at 70%. There are significant differences in students' analytical abilities in distinguishing, organizing, and attributing using Virtual Reality media compared to those who do not participate in Virtual Reality media learning in biology subject XI MIPA. This research recommended to pay greater attention to the use of suitable learning material, as well as to create additional space and facilities for instructors and students to use throughout the learning process. Also, the school must provide new breakthroughs in learning, such as updating up-to-date or up-to-date learning media and educating instructors to design and apply them.